Synthesis, Docking and Antimicrobials Evaluation of Novel Pyrazolotriazines as RNA Polymerase Inhibitors - Abdallah, Amira; Elgemeie, Galal; Ahmed, Ebtsam (Current Organic Chemistry, 2021)
Aims: Producing novel pyrazolotriazines such as pyrazolo[1,5-a][1,3,5]triazine and pyrazolo[5,1-c][1,2,4]triazine derivatives and evaluate their biological activity as antimicrobial agents followed by the Minimum Inhibitory Concentration (MIC) for the most active compounds. Moreover, study the molecular docking and the RNA polymerase inhibitory activity. Background: Pyrazolotriazine derivatives considered one of the most important heterocyclic compounds due to their broad biological activities. Due to the similarity with the purines and thioguanines, the pyrazolo[1,5-a][1,3,5]triazine and pyrazolo[5,1-c][1,2,4]triazine compounds were used as antimetabolic agents. Moreover, many approved drugs contain pyrazolo[1,5- a][1,3,5]triazine ring systems such as (1882L04 and SB-H02), which confirmed the pharmaceutical applications. The key precursor 5-aminopyrazoles 3 which were firstly synthesized by our research group, were used to prepare the novel pyrazolotriazine derivatives. Objective: This study aimed to synthesize novel bioactive pyrazolo[1,5-a][1,3,5]triazine and pyrazolo[5,1- c][1,2,4]triazine derivatives as antimicrobial agents. Also, the Minimum Inhibitory Concentration (MIC) for the most potent compounds was evaluated. On the other hand, the molecular docking study and the RNA polymerase inhibitory activity were measured. Methods: In this work, the 5-aminopyrazoles 3 were used to synthesize 4-amino-7-(arylamino)pyrazolo[1,5- a][1,3,5]triazine-8-carboxamides 7a-c, 4-amino-7-(arylamino)-2-thioxo-1,2-dihydropyrazolo[1,5-a][1,3,5]-triazine- 8-carboxamides 10a-c and 4-amino-3-cyano-7-(aryllamino)pyrazolo[5,1-c][1,2,4]triazine-8-carboxamides 12ac. The newly resultant compounds were evaluated as antibacterial agents by using (Gram-positive bacteria) such as [Staphylococcus aureus and Streptococcus mutans], and (Gram-negative bacteria) such as [Escherichia coli, Pseudomonas aeruginosa, and Klebsiella]. Moreover, the new compounds were evaluated as antifungal agents by using Candids Albicans fungal strain. Also, the Minimum Inhibitory Concentration (MIC) for the most potent compounds was measured. For all the synthesized compounds, the molecular docking studies were recorded and the RNA polymerase inhibitory activity was measured for the high docking score compounds. Results: The results revealed that most of the prepared compounds such as 7b, 10b, 10c, 12a, 12b, and 12c showed moderate activity towards some of the used strains. The MIC evaluations were recorded for the most active tested compounds 7b, 10b, 10c, 12a and 12c. On the other hand, the most potent and the high docking score compounds (10c, 12a and 12c), were measured in vitro to inhibit RNA polymerase enzyme. Conclusion: A number of novel bioactive pyrazolo[1,5-a][1,3,5]triazine and pyrazolo[5,1-c][1,2,4]triazine derivatives were synthesized. All the resultant compounds were screened for their antimicrobials activity and the MIC test was measured for the most potent compounds. In addition, the in vitro to inhibit RNA polymerase enzyme was evaluated for the most active high docking score compounds. Other: Most of the heterocyclic ring systems have remarkable activities in all fields, especially in pharmaceutical applications.
Keywords: pyrazolotriazine